Enantiomeric Discrimination by Surface‐Enhanced Raman Scattering–Chiral Anisotropy of Chiral Nanostructured Gold Films. (21st June 2020) - Liu, Zexi; Ai, Jing; Kumar, Prashant; You, Enming; Zhou, Xiong; Liu, Xi; Tian, Zhongqun; Bouř, Petr; Duan, Yingying; Han, Lu; Kotov, Nicholas A.; Ding, Songyuan; et al.
Abstract: A surface‐enhanced Raman scattering‐chiral anisotropy (SERS‐ChA) effect is reported that combines chiral discrimination and surface Raman scattering enhancement on chiral nanostructured Au films (CNAFs) equipped in the normal Raman scattering Spectrometer. The CNAFs provided remarkably higher enhancement factors of Raman scattering (EFs) for particular enantiomers, and the SERS intensity was proportional to the enantiomeric excesses ( ee) values. Except for molecules with mesomeric species, all of the tested enantiomers exhibited high SERS‐ChA asymmetry factors ( g ), ranging between 1.34 and 1.99 regardless of polarities, sizes, chromophores, concentrations and ee . The effect might be attributed to selective resonance coupling between the induced electric and magnetic dipoles associated with enantiomers and chiral plasmonic modes of CNAFs. Abstract : Absolution by SERS : A surface‐enhanced Raman scattering chiral anisotropy effect is presented that combines chiral discrimination and surface Raman scattering enhancement on chiral nanostructured Au films. It is applied in the normal Raman scattering system to identify the absolute configuration and composition of enantiomers, overcoming disadvantages of polarimeter systems and chromatography.